The Myth of Civil Society’s Democratic Role: Volunteerism and Indonesian Democracy - Hurriyah, Hurriyah (Jurnal Politik, 2019)
Is a flourishing civil society’s political activism positively correlated with the deepening of Indonesian democracy? This article addresses this question by examining the role of civil society in the 2014 presidential election in Indonesia, focusing on the collective actions of volunteer groups (known as Gerakan Relawan) that shaped both the election process and its result. While some studies on civil society activism in the 2014 presidential election suggested the connection between the role of volunteer movement and the democratic process in Indonesia, this paper suggests that the overpraised assumptions regarding the connection between civil society’s role and democratic consolidation, in the case of volunteer movement, needs to be reconsidered. This paper argues that although the activism of the volunteer movement has positively contributed to the democratic process of the 2014 election, however, realistic assessment of the volunteer movement confirms its problematic nature and the limits of volunteer activism that may contribute to the disconnection of civil society and democratic consolidation in the country.